Response of Three Shade Tree Species to Grass and Woodchip Mulching - Tasan, John (2002)
The tree loss in urban areas is of major concern because they represent shortfalls in the management objectives and waste money for replanting programmes. Mulching is considered as the best alternative for enhancing tree growth and to rehabilitate degraded urban soil. This study was carried out to examine the relative growth of 180 transplanted seedlings of Cinnamomum iners, Hopea odorata and Mimusops elengi in response to grass, woodchip and control mulching after 28 months. The data on collar diameter, height, volume, and fine root biomass was analysed using two-way analyses of variance, including comparison of mean values. The results showed that Cinnamomum iners, Hopea odorata and Mimusops elengi showed better diameter, height, volume and fine root growths when treated with the various mulch treatments (p::;;0.05). The reasons for these results are discussed. Generally, it was found that Hopea odorata and Cinnamomum iners have better growth when treated with the grass mulch, while Mimusops elengi showed better growth when treated with the woodchip mulch.